2021
DOI: 10.3389/fcimb.2021.752275
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Urinary Infection in Overactive Bladder Syndrome: A Prospective, Blinded Case Control Study

Abstract: ObjectivesTo investigate whether women with overactive bladder (OAB) symptoms and no evidence of clinical infection by conventional clean-catch midstream urine cultures have alternative indicators of sub-clinical infection.Patients/Subjects, Materials & MethodsThe study was a prospective, blinded case-control study with 147 participants recruited, including 73 OAB patients and 74 controls. The OAB group comprised female patients of at least 18 years of age who presented with OAB symptoms for more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Additionally, multiple studies have pointed out that the occurrence of OAB is related to tract infections [ 50 52 ]. Khan Zainab’s research confirmed that patients with OAB symptoms have significant bacterial growth on enhanced urine culture, which is often undetectable through routine culture, suggesting the possibility of subclinical infection [ 53 ]. A higher likelihood of tract infection was observed in sexually active women.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multiple studies have pointed out that the occurrence of OAB is related to tract infections [ 50 52 ]. Khan Zainab’s research confirmed that patients with OAB symptoms have significant bacterial growth on enhanced urine culture, which is often undetectable through routine culture, suggesting the possibility of subclinical infection [ 53 ]. A higher likelihood of tract infection was observed in sexually active women.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when both standard (10 5 CFU/ml) and low-count criteria (10 2−3 CFU/ml) are used in samples from the same patient cohort, the proportion of those positive for bacteriuria increases (from 17% to 39%), compared to those of a control group (from 2% to 6%) ( Walsh et al, 2011 ) showing that low-count MSU culture may reveal genuine infections in OAB patients that would otherwise be overlooked. Enhanced culture techniques have also revealed higher rates of infection that were previously missed by routine culture, identifying 23% of patients with OAB as positive for UTI, vs. 10% of controls, in a prospective blinded case control study ( Khan et al, 2021 ).…”
Section: The Emerging Role Of Urinary Tract Infection In Overactive B...mentioning
confidence: 99%
“…High-throughput DNA sequencing and enhanced culture-based investigations have found bacterial DNA and live bacteria, respectively, in catheterized (bladder) urine deemed culture-negative by the standard urine culture method [1][2][3][4][5][6][7][8][9][10][11][12][13]. The expanded quantitative urine culture (EQUC) protocol and similar enhanced (metaculturomic) methods have enabled researchers to isolate species detected by 16S rRNA gene sequencing in both individuals with and without urinary tract symptoms [7,8,11,[13][14][15]. While the genetic diversity of some species has been extensively investigated, e.g., Escherichia coli [16,17], many species have few or no genomic sequences.…”
Section: Introductionmentioning
confidence: 99%